Comparing Genotyping‐by‐Sequencing and Single Nucleotide Polymorphism Chip Genotyping for Quantitative Trait Loci Mapping in Wheat. Issue 1 (1st January 2016) - Bajgain, Prabin; Rouse, Matthew N.; Anderson, James A.
ABSTRACT: Array‐ or chip‐based single nucleotide polymorphism (SNP) markers are widely used in genomic studies because of their abundance in a genome and lower cost per data point than older marker technologies. Genotyping‐by‐sequencing (GBS), a relatively newer approach of genotyping, suggests equal appeal because of its lesser cost per data point and the avoidance of ascertainment bias during genotyping. In this study, we compared the results from quantitative trait loci (QTL) mapping, marker distribution on linkage maps, genome size, recombination sites covered by the markers, and cost per polymorphic marker, as well as the methodology and workflow between the Illumina Infinium 9000 SNP‐chip genotyping with GBS. Results indicate that while GBS offers similar genome coverage at almost one‐fourth the cost of SNP chip, the SNP‐chip method is less demanding of computational skills and resources. Eight and nine QTL were detected in the GBS and SNP‐chip datasets, respectively, with one QTL common between the systems. Additionally, imputation accuracy of the GBS dataset was examined by introducing missing values randomly and imputing the missing alleles using a probabilistic principal components algorithm. Imputation results suggest recovery of the missing alleles with reasonable accuracy in datasets with low (up to 40%) amount of missing data is possible and can provide acceptable accuracy in gene mapping. Overall, the comparative results indicate that both approaches provide good genome coverage and similar mapping results. The choice of the genotyping platform is decided by the nature of the study and available resources.